The right to challenge arbitrators: urgent need for reform with regard to public contracting - Martin Tirado, Richard (2016)
Concerning the entry into force of the Law 30225, new Public Contracting Law, and its rules of procedure, in this article, the author analyzes the institution of the right to challenge arbitrators in the field of public contracting. In his analysis, the author examines the right to challenge arbitrators as is set forth in other legal bodies, taking note of the issues that may be present with its transfer to the public contracting area –given its particularities–, and finally concludes that an urgent reform in this matter is needed.